Chemical and physical-mechanical characterizations of cement with the addition of limestone filer in Venezuela - Bolognini, H.; MartínezN.; Troconis de Rincón, O. (Revista ALCONPAT, 2015)
In recent years in Venezuela, there has been a crisis on demand, production and marketing of cement, primary building material. In this work the chemical and physical mechanical characterization made a Top Trademark blended cements in the country, characterizing them according to: chemical composition, Blaine fineness, setting time and compressive strength. The results show that these cements do not meet the minimum requirements established in the Venezuelan standard for use in the manufacture of structural concrete. Keywords: Blended cement, Corrosion, Reinforced Concrete.